2016
DOI: 10.1021/acs.analchem.6b01630
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fragment Ion Information as Further Evidence in Probabilistic Compound Screening Using Bayesian Statistics and Machine Learning: A Leap Toward Automation

Abstract: In this work, we introduce an automated, efficient, and elegant model to combine all pieces of evidence (e.g., expected retention times, peak shapes, isotope distributions, fragment-to-parent ratio) obtained from liquid chromatography-tandem mass spectrometry (LC-MS/MS/MS) data for screening purposes. Combining all these pieces of evidence requires a careful assessment of the uncertainties in the analytical system as well as all possible outcomes. To-date, the majority of the existing algorithms are highly dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…Unfortunately, most currently existing open-source/commercial software packages are not equipped to efficiently handle the large, high-resolution data sets, thus usually applying some sort of data reduction or preprocessing, vulnerable to discarding valuable information too early in the data analysis pipeline, resulting in a propagated error affecting the compound identification step. In our previous work ,, we had demonstrated that probabilistic peak detection is superior to deterministic algorithms and have shown that it outperforms widely used existing algorithms. In this work, a novel, fully untargeted, faster, and efficient probabilistic feature recognition algorithm based on artificial neural network (ANN) for LC–HRMS data has been developed, and its usefulness in forensic and food safety toxicology context has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, most currently existing open-source/commercial software packages are not equipped to efficiently handle the large, high-resolution data sets, thus usually applying some sort of data reduction or preprocessing, vulnerable to discarding valuable information too early in the data analysis pipeline, resulting in a propagated error affecting the compound identification step. In our previous work ,, we had demonstrated that probabilistic peak detection is superior to deterministic algorithms and have shown that it outperforms widely used existing algorithms. In this work, a novel, fully untargeted, faster, and efficient probabilistic feature recognition algorithm based on artificial neural network (ANN) for LC–HRMS data has been developed, and its usefulness in forensic and food safety toxicology context has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The mass spectrometer was operated in positive electrospray mode with an acquisition at 70 000 resolving power. Further details can be found on Materials and Methods section of refs and for the two data sets, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coming back to machine learning, it is worthwhile to mention that these techniques are increasingly applied to design of experiments, cf. . The goal is to build self‐learning, self‐monitoring and self‐optimizing chemical plants which plan and perform new experiments itself without using any further human resources.…”
Section: Model‐based Design Of Experimentsmentioning
confidence: 99%
“…In this work, we introduce a novel probabilistic approach for peak detection in CE‐LIF epg's from STR DNA profiling data. Our Bayesian framework has been originally developed and introduced for chromatographic‐mass spectrometric data in analytical chemistry and proved to be ideally suited for this purpose . We theorize that the statistical evaluation of low‐level (complex) DNA profiles will be enhanced by including probabilistic peak detection data which are generated directly from CE data.…”
Section: Introductionmentioning
confidence: 99%